Molecular analyses in Indonesian individuals with intellectual disability and microcephaly - Farmaditya EP Mundhofir; Rahajeng N Tunjungputri; Willy M Nillesen; Bregje WM van Bon; Martina Ruiterkamp-Versteeg; Tri I Winarni; Ben CJ Hamel; Helger G Yntema; Sultana MH Faradz (Paediatrica Indonesiana, 2013)
Background Intellectual disability (ID) often coincides with anabnormal head circumference (HC). Since the HC is a reflectionof brain size, abnormalities in HC may be a sign of a brain anomaly.Although microcephaly is often secondary to ID, hereditary(autosomal recessive) forms of primary microcephaly (MCPH)exist that result in ID.Objective To investigate mutations in MCPH genes in patientswith ID and microcephaly.Methods From a population of 527 Indonesian individuals withID, 48 patients with microcephaly (9.1 %) were selected. Thesepatients were previously found to be normal upon conventionalkaryotyping, fragile X mental retardation 1 (FMRl) gene analysis,subtelomeric deletion, and duplication multiplex ligationdependentprobe amplification (MLPA). Sanger sequencing forabnormal spindle-like microcephaly-associated (ASPM) and WDrepeat domain 62 (WDR62) was performed in all 48 subjects, whilesequencing for microcephalin (MCPHl), cyclin-dependent kinase5 (CDK5) regulatory subunit-associated protein 2 (CD5KRAP2) ,centromere protein} (CENPJ), and SCUfALl interrupting locus(STIL) was conducted in only the subjects with an orbitofrontalcortex (OFC) below -4 SD.Results In all genes investigated, 66 single nucleotide polymorphisms(SNPs) and 15 unclassified variants which were predictedas unlikely to be pathogenic (lN2), were identified. Possiblepathogenic variants (lN3) were identified in ASPM. However,since none of the patients harboured compound heterozygouslikely pathogenic mutations, no molecular MCPH diagnosis couldbe established. Interestingly, one of the patients harboured thesame variants as her unaffected monozygotic twin sister, indicatingthat our cohort included a discordant twin.Conclusions This study is the first to investigate for possible geneticcauses ofMCPH in the Indonesian population. The absenceof causative pathogenic mutations in the MCPH genes tested may originate from several factors. The identification of UV2and UV3 variants as well as the absence of causative pathogenicmutations calls for further investigations.